Using Behavioral Indicators to Help Detect Potential Violent Acts A Review of the Science Base - Davis, Paul K. (RAND Corporation, 2013)
Government organizations have put substantial effort into detecting and thwarting terrorist and insurgent attacks by observing suspicious behaviors of individuals at transportation checkpoints and elsewhere. This report reviews the scientific literature relating to observable, individual-level behavioral indicators that might, along with other information, help detect potential violent attacks.